Validation of TWIST (Testicular Workup for Ischemia and Suspected Torsion) Score System for Differential Diagnosis in Acute Scrotum in Tertiary Teaching Hospital - Nyoman Gede Prayudi; Besut Daryanto; Taufiq Nur Budaya (Jurnal Kedokteran Brawijaya, 2022)
The acute scrotum is a common urological emergency and has a broad differential diagnosis. There is no clear consensus on a particular algorithm to follow in the diagnosis of testicular torsion. Testicular Workup for Ischemia and Suspected Torsion (TWIST) Score, a risk scoring system based on signs and symptoms, can be invaluable in managing patients with the acute scrotum, specifically testicular torsion. This study aimed to evaluate the effectiveness of the TWIST scoring system for differential diagnosis of acute scrotal patients. The study was conducted using secondary data, medical records from 111 male patients diagnosed with acute scrotum in Saiful Anwar General Hospital Malang between January 2015 and December 2018. Data about the onset of pain, first contact, history, physical examination findings, any adjunct test performed, and intra-operative findings were collected. The effectiveness of the TWIST score in diagnosing testicular torsion was determined by calculating the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). Of the 111 patients, 43 patients (38.7%) had testicular torsion. The mean age was 17.49 (6.69) years. A total of 39 patients were classified as high risk as per the TWIST Score with cut point 5 had 83.7% sensitivity, 95.6% specificity, 92.3% positive predictive value (PPV), and 90.3% negative predictive value (NPV). The area under the curve was 0.93. The use of the TWIST Score in clinical practice can accurately determine high-risk patients who can proceed straight to the operating theatre without the need for an ultrasound.